Obstructive sleep apnoea and bone health. Issue 4 (October 2016) - Liguori, Claudio; Piccirilli, Eleonora; Izzi, Francesca; Mercuri, Nicola Biagio; Tarantino, Umberto; Placidi, Fabio
We thank J-Y. Zhong and L-Q. Yuan for their comments on our paper investigating bone mineral density (BMD) in male obstructive sleep apnoea (OSA) patients [1]. In our report, published in the European Respiratory Journal [1], we documented that male patients with severe OSA (apnoea–hypopnoea index >30 events·h −1 ) show a severely decreased BMD in the lumbar spine and femur compared with male controls matched for age, body mass index and physical activity. We also documented that OSA patients present an increased risk for osteopenia and osteoporosis. In keeping with our findings, Chi-squared analysis corrected for continuity showed that T-scores consistent with osteopenia/osteoporosis were more frequent in OSA patients compared with controls at all regions of the lumbar spine and at the femur neck, upper femur neck and Ward triangle [1]. Obstructive sleep apnoea represents a risk factor for osteopenia and osteoporosis in male patients at all ages http://ow.ly/c9Tn302PPKz